Influence of incubation period on membrane patch color for insoluble contaminant measurement in degraded hydraulic oils - Pravda, Stepan; Sedenka, David; Blata, Jan; Hrabovsky, Leopold (Frontiers in Mechanical Engineering, 2024)
Insoluble contaminants and varnish, resulting from oil degradation byproducts and sometimes depleted additive molecules, are initiated primarily due to thermal stress on the oil. This poses significant challenges in tribology, particularly for the lubrication systems of modern complex machinery, leading to severe debilitating effects such as loss of operating clearances and impaired heat transfer. Addressing varnish buildup is crucial, and timely oil analysis emerges as a valuable tool, offering essential insights into the oil degradation level and the potential presence of insoluble contaminants. Among the various laboratory testing methods available to assess varnish potential, colorimetric analysis, specifically Membrane Patch Colorimetry (MPC), is widely applied owing to its efficiency and cost-effectiveness. This study extends the application of MPC test principles, commonly utilized for turbine oils, to measure insoluble contaminants generated by degraded hydraulic fluids. Adhering to the ASTM D7843-21 standard, which stipulates the precision of this testing method for turbine oils is contingent upon the sample’s incubation period, our investigation focuses on exploring modifications to the standard 72-hour incubation period. We aim to assess the viability of shortening or extending this duration for conducting MPC tests on used hydraulic fluids, thereby potentially enhancing the precision and relevance of MPC tests in hydraulic fluid analysis.